Thiol-dependent proteases of African trypanosomes: Analysis by electrophoresis in sodium dodecyl sulphate/polyacrylamide gels co-polymerized with fibrinogen - Londsdale-Eccles, J.D.; Mpimbaza, G.W.N. (Wiley, 1986)
The proteases of several species of African trypanosomes were analysed by electrophoresis in sodium dodecyl sulphate/polyacrylamide gels containing fibrinogen or collagen. After electrophoresis the gels were incubated in the presence of enzyme activators and/or inhibitors and then stained with Coomassie brilliant blue. The areas where the proteolytic activity had degraded the fibrinogen did not stain and so formed clear bands against a blue background. The proteases were found to have pH optima between 5 and 6, and required dithiothreitol or 2‐mercaptoethanol for full expression of their activity. They were inhibited by amino acid chloromethanes, iodoacetamide, p‐chloromercuribenzoate and other inhibitors of the thiol‐dependent proteases, as well as by the trypanocidal drugs berenil® (4,4′‐diamidinodiazoaminobenzene‐diacetamidoacetate) and pentamidine [1,5‐di‐(4‐amidinophenoxy)pentane‐di‐(2‐hydroxyethanesulphonate)]. Trypanosoma evansi, Trypanosoma brucei brucei and Trypanosoma brucei gambiense each have a protease with a relative molecular mass, Mr, of 28000. In addition they occasionally exhibit activity at higher Mr values (up to 105000). Trypanosoma congolense has a low‐Mr protease (31000) and may exhibit higher‐Mr proteases (up to 150000). The protease profiles of Trypanosoma vivax differ from the other species, T. brucei or T. congolense, and are present in lesser amounts. The proteases of the cultured procyclic forms are present in much smaller amounts than those of the metacyclic or mammalian blood stream forms of these parasites. The catalytic properties and inhibition characteristics of these thiol‐dependent enzymes suggest that they resemble the mammalian lysosomal cathepsins B and L.